Factors Influencing the Probability of Viral Online Purchase for Agricultural Products - Thathong, Piyathida; Sayruamyat, Suwanna; Potchanasin, Chakrit (Journal of Business, Innovation and Sustainability (JBIS), 2022)
The aim of this paper is to critically investigate factors determine probability of viral online purchase for agricultural products. The study was conducted in the form of survey, with data being gathered via questionnaires from 271 respondents who aged between 22-60 years old and analyzed by ordered probit model. The results show that subjective norms, perceived behavioural control, satisfaction and trust in the system of buying agricultural products online significantly influences the probability of viral online purchase for agricultural products. These results suggest that farmers and agribusiness operators should pay close attention to after-sales services, such as checking the quality of products and solving customer issues immediately. It would increase the possibility of word-of-mouth.